2004
DOI: 10.1038/sj.onc.1207878
|View full text |Cite
|
Sign up to set email alerts
|

Aberrations of the Chk2 tumour suppressor in advanced urinary bladder cancer

Abstract: Checkpoint kinase 2 (Chk2) is a tumour suppressor and signal transducer in genome integrity checkpoints that coordinate cell-cycle progression with DNA repair or cell death in response to DNA damage. Defects of Chk2 occur in subsets of diverse sporadic malignancies and predispose to several types of hereditary carcinomas. However, the status of Chk2 in tumours of the urinary bladder remains unknown. Here, we report that among 58 advanced (grade T2-T4) human bladder carcinomas, immunohistochemical analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…The reliability of the ligation assay was confirmed by re-analysis of 248 DNA samples from WECARE Study participants using denaturing gradient gel electrophoresis (DGGE), as described previously (Bartkova et al, 2004). We found complete concordance between the results obtained with these two methods (3 out of 248 samples screened were positive for mutations).…”
Section: Genotyping Of Chek2*1100delcsupporting
confidence: 69%
“…The reliability of the ligation assay was confirmed by re-analysis of 248 DNA samples from WECARE Study participants using denaturing gradient gel electrophoresis (DGGE), as described previously (Bartkova et al, 2004). We found complete concordance between the results obtained with these two methods (3 out of 248 samples screened were positive for mutations).…”
Section: Genotyping Of Chek2*1100delcsupporting
confidence: 69%
“…Germline CHEK2 mutations have been associated with an increased risk of breast, prostate, colon cancers, thyroid, kidney, low-grade ovarian cancers and lymphomas, but bladder cancer has not been studied extensively. 1,11,[12][13][14][15][16]19,21,24,25 Two previous reports suggest that individuals with mutations in the CHEK2 gene might be at increased risk of bladder cancer. 13,14 To confirm this hypothesis, we have genotyped 416 incident cases of bladder cancer and 3,313 controls for the 4 CHEK2 founder mutations present in the Polish population.…”
mentioning
confidence: 99%
“…7,[12][13][14][15][16][17]19,21,22 The first mutations in CHEK2 which were reported in sporadic and hereditary cancers indicated that CHEK2 defects might explain the tumor-prone phenotype in families with Li-Fraumeni syndrome (LFS). 1,12,13,15,17,18,23 To date CHEK2 mutations have been found in subset of human breast carcinomas, testicular tumors and lymphomas. Germline CHEK2 mutations have been associated with an increased risk of breast, prostate, colon cancers, thyroid, kidney, low-grade ovarian cancers and lymphomas, but bladder cancer has not been studied extensively.…”
mentioning
confidence: 99%
See 2 more Smart Citations